2015
DOI: 10.1093/jisesa/iev019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Cuticular Protein Glycine-Rich13 Gene Expression in Wing Disc of Bombyx mori, Lepidoptera

Abstract: Cuticular protein genes are good models to study the molecular mechanisms of signaling by ecdysteroids, which regulate molting and metamorphosis in insects. The present research demonstrates on hormonal regulation and analysis of the regulatory sequences and transcription factors important for Bombyx mori cuticular protein glycine-rich13 (CPG13) gene expression. Expression of CPG13 was strong at prepupal stage in wing tissues of B. mori. CPG13 expression was induced by the addition of 20E, which was inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Current studies have showed that BR-C, E74A and βFTZ-F1 regulate different cuticular protein genes [9,10,11,16,17,20]. Thus, these ecdysone-responsive transcription factors are suggested to regulate their target genes, and the series of their expression would bring about insect metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies have showed that BR-C, E74A and βFTZ-F1 regulate different cuticular protein genes [9,10,11,16,17,20]. Thus, these ecdysone-responsive transcription factors are suggested to regulate their target genes, and the series of their expression would bring about insect metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cuticular protein genes, which have different developmental profiles, were induced by different types of ecdysone signal, and these things were described in a recent review [7].The determination of insect genomic sequences also brought about the comprehensive analysis of cuticular-protein gene expression and the analysis of its regulation by transcription factors [8][9][10][11][12][13][14][15][16][17]. Cuticular protein genes have different expression profiles [8][9][10][11][12][13][14][15][16][17] and regulatory systems by ecdysone-responsive transcription factors [9][10][11][12][13][14][15][16][17][18][19]. From this, insect cuticular protein genes are suggested to be a suitable material for clarifying the regulatory mechanism of ecdysone-responsive transcription factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using NCBI and UniProt BLAST the Vajk proteins were found to be 49 to 80% identical to several cuticular proteins identified in other insect species, such as Bombyx mori (Ali et al, 2015;Suetsugu et al, 2013), Danaus plexippus (Zhan et al, 2011), Operophtera brumata (Derks et al, 2015), Anopheles gambiae (He et al, 2007), Papilio polytes (Futahashi et al, 2012) and Papilio xuthus Futahashi et al, 2012).…”
Section: Molecular Characteristics Of the Vajk Proteinsmentioning
confidence: 81%
“…Developmental profiles and reporter assays also suggest that the expression of Group 3 CP genes BmorCPH33 and BmorCPR34 is regulated by BHR4 (44,59). Group 4 expression is believed to be regulated by BR-C, as the expression profiles of BmorCPG11, BmorCPG13, and BmorCPH30 are similar to the expression profile of BR-C, and a BR-C binding site is located upstream of BmorCPG11 and BmorCPG13 (47,48,60) (48 Ref3). The expression of the Group 5 genes can be observed after the wandering stage.…”
Section: Responsiveness Of Prepupal Cp Genes To Ecdysone Influences the Developmental Profiles Of Ecdysone-responsive Transcription Factomentioning
confidence: 99%